TEMPORAL DISTRIBUTION OF ARTHROPODS IN Borreria repens DC. AND Setaria sp. WILD PLANT SPECIES IN TEA PLANTATION AREA OF WONOSARI SINGOSARI - MALANG DISTRICT - Anggun Wulandari (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2018)
The temporal distribution of Athropods, it saw from arthropod frequency visiting to Borreria repens DC and Setaria sp. in time of observation. This research was aim to understanding Arthropod temporal distribution in Borreria repens DC and Setaria sp. wild plant in tea plantation area of Wonosari Singosari – Malang disctrict. The data collection method using the "visual control" developed by Frei and Manhart (1992) which has been modified. This research conducted in tea plantation area of Wonosari Singosari – Malang disctrict in pebruary – march 2016. Observation of amount arthropoda in Borreria repens DC. conducted at time 07.00-07.15, 08.00-08.15, 09.00-09.15, 10.00-10.15, 11.00-11.15, 12.00-12.15, 13.00-13.15, 14.00-14.15, 15.00-15.15, 16.00-16.15 and 17.00-17.15. Observation of amount arthropoda in Setaria sp. conducted at time 07.20-07.35, 08.20-08.35, 09.20-09.35, 10.20-10.35, 11.20-11.35, 12.20-12.35, 13.20-13.35, 14.20-14.35, 15.20-15.35, 16.20-16.35 and 17.20-17.35. The result of this research showed: arthropoda families that active in morning and afternoon time is Cicadellidae; arthropoda families that active only in the morning is Dolichopodidae and Syrpidae; arthropoda families that active in all time is Coccinellidae, Formicidae, Lycosidae, Oxyopidae, Geometridae and Mantidae.